Pembuatan Pupuk Organik Berbahan Sampah Organik Rumah Tangga Dengan Penambahan Aktivator EM 4 Di Daerah Kayu Tangi - Novi Rahmawanti; Novrian Dony (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2014)
Banjarmasin covered by swamp area almost 32 %. Accumulation of organic waste make this area looks not clean fully especially around people’s house. The people tend burn them to make its look clean, but they dont know how danger it is. Less knowledge as principally factor. They dont know that they cause ISPA, air pollution, and danger one is burning disaster. The way to overcome this by make them be a valuable thing by compost them to be compost fertilizer. In this research, compost fertilizer was made by addition EM4 activator and compered by cow waste dan commercial fertilizer. Composting by using EM4 is faster 20 days at water content 40.06 %, pH 7.3, Organic C 20%, totally nitrogen 1.51%, P 1.50%, K 2.66%, Fe 0.75%, dan Zn 89 ppm and still fullfill SNI qualification. This Compost fertilizer give positive effect to the plant.